From sacrificio to egoísmo : generation '75 in urban Galicia and the Spanish fertility rate - White, Amanda Lynn, 1976- (2000)
Thesis (M.A.)--Memorial University of Newfoundland, 2001. Anthropology Bibliography: leaves 216-234 At 1.07. the Spanish fertility rate is currently one of the lowest in the world and is depicted by politicians as constituting a public ‘crisis’. The fieldwork that I conducted in Lugo (Galicia) focused on local level interpretations of the fertility decline. Drawing on Michael Herzfeld's concept of "cultural intimacy" (1997). I explore in the first part of the thesis, the interconnection between the state's emphasis on the ‘bettering’ of the nation through an increase in population numbers, and citizens’ focus on the ‘bettering’ of children through attentive and child-centered raising practices. In the second part of the thesis, I examine the interrelation between socioeconomic changes and shifts in gender ideologies as these relate to what people frequently told me is a main reason for the decline: that young women are behaving in a ‘masculine’ way by displaying egoismo (selfishness or self-centeredness). I look at how young people talk about the links between notions of gender difference and the 'low’ fertility rate. I follow a post-structuralist approach in my analysis of the cultural construction of ‘being selfish’ which moves beyond previous research on gender in southern Europe. Moreover, I focus particularly on how young women experience the public criticisms of their femininity and I ask how this relates to their sense of identity and notions of motherhood. In addition to previous anthropological work on demographic patterns and the body-politic, the analysis-through the employment of Herzfeld's "social poetics’’ (1985 and 1997)-of the interplay between the ambiguous relationship of everyday practices, performances, and discourses adds context to Spain's "fertility puzzle" and people's interpretations of it.